Mechanism of clarification of colloidal suspension using composite dry powdered flocculant - Kadooka, Hiroto; Jami, Mohammed Saedi; Tanaka, Takanori; Iwata, Masashi (Elsevier Inc., 2016)
Flocculation is a widely used process for particle removal in water/wastewater treatment. Clarification method by using composite flocculants in powder form has been proposed in the literature. Such composite flocculants are conveniently used in the flocculation process of small volume suspensions. In this study, fundamental aspects of the clarification mechanism of the composite dry powdered flocculant are investigated. 1.00 mg/mL suspension of polymethyl methacrylate particle (PMMA, 0.15 m in diameter) is used as a colloidal material. A model composite flocculant comprising an inorganic flocculant (aluminum sulfate), anionic polymer flocculant (copolymer of acrylic acid and acrylic amide), and a flocculation aid (calcium carbonate) is studied. The effects of each component on turbidity removal are examined. It is clarified that the order of addition, the state of polymer flocculant (powdered form or liquid form), and combination of components (polymer flocculant with/without aid particles) are critical for turbidity removal with combined use of flocculation aid, inorganic flocculant and polymer flocculant. When the composite dry powdered flocculant is added to a colloidal suspension, the inorganic flocculant dissolves immediately. The polymer flocculant particles disperse well in the suspension with the help of flocculation aid particles and dissolve moderately. The ions from inorganic flocculant result in formation of microflocs composed of both PMMA and flocculation aid particles. Flocculation aid particles play an important role;i.e.they accelerate flocculation of PMMA particles and attenuate the ability ofthe polymer flocculant particles to produce undissolved lumps.